2020
DOI: 10.5897/jpp2020.0591
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening and antimicrobial activities of hydroethanolic extracts from leaves and roots of Cochlospermum planchonii (Bixaceae)

Abstract: Cochlospermum planchonii is traditionally used in Togo in treating several diseases, including burn wounds which achievement requires anti-infective and good cicatrisation processes. This study aims to evaluate the antimicrobial properties of hydroethanolic extracts from leaves and roots of C. planchonii and its phytochemical composition. Five (05) bacterial strains were suspended in liquid media with plant extracts at various concentrations and then spread, after 24 h incubation, on solid media. The minimum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Regarding mechanisms, our previous data (Fankibe et al, 2020) have reported the presence of metabolites (flavonoids, tannins, carbohydrates, sterols, triterpenes, and saponosides) in the leaves and root hydroethanolic extracts of this plant, as also reported elsewhere (Da et al, 2015;Kallo et al, 2018). In fact, many studies that have highlighted the variations in concentration of secondary metabolites from plant to plant species as well as in the different parts of a plant, leaves and roots being the preferential sites of accumulation of these compounds (Kantati et al, 2016).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Regarding mechanisms, our previous data (Fankibe et al, 2020) have reported the presence of metabolites (flavonoids, tannins, carbohydrates, sterols, triterpenes, and saponosides) in the leaves and root hydroethanolic extracts of this plant, as also reported elsewhere (Da et al, 2015;Kallo et al, 2018). In fact, many studies that have highlighted the variations in concentration of secondary metabolites from plant to plant species as well as in the different parts of a plant, leaves and roots being the preferential sites of accumulation of these compounds (Kantati et al, 2016).…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies in our laboratory have shown the presence of secondary metabolites such as flavonoids, tannins, carbohydrates, sterols, triterpenes, and saponosides in the leaves and root hydroethanolic extracts of this plant (Fankibe et al, 2020). Elsewhere, numerous pharmacological properties have been reported, including: anti-malarial activity in vitro against Plasmodium falciparum (Benoit-Vical et al, 2001); anti-inflammatory and antihyperglycemic properties (Yoda et al, 2020); hepatoprotective activity (Anaga and Oparah, 2009), inhibitory activity on Toxoplasma Gondii (Benoit-Vical et al, 2000), anti-microbial proprieties (Isah et al, 2013;Fankibe et al, 2020). Our objective in approaching this work was to evaluate the healing effect of this plant on skin burns model in mice.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The methanol root extract of Cochlospermum tinctorium was effective in inhibiting the isolates at high concentration of 10 mg mL -1 on S. aureus and Listeria monocytogene in the study of Abdulaziz et al (2019). Fankibe et al (2020) found satisfactory antibacterial activity on S. aureus by evaluating the extract of C. planchonii leaves and roots. Menezes Filho et al (2020) verified important antifungal activity of the essential oil of the C. regium flower on the phytopathogen Sclerotinia sclerotiorum with an inhibition rate of 79.98% (100 µL mL-1).…”
Section: Resultsmentioning
confidence: 97%